Teacher’s Effort in Guiding Emotion of Students - Yulidar Ibrahim; Annisa Pertiwi (Universitas Negeri Padang, 2020)
Teachers are expected to guide students to achieve optimal development through teaching-learning process especially to students who face difficulties at school; for instance, unstabilize their emotion. Because of this unstable emotion, it is impacted to relationship harmony between teacher and the students itself. The goal of this article to discuss teachers’ effort in guiding emotion of students in the scope of: teenager and their developmental duties, emotional development and youngster’ emotional maturity, teacher/parent efforts in fostering adolescent development.